Laju Urbanisasi dan Pertumbuhan Kota di Indonesia - Abdul Rahman (PREDESTINATION: Journal of Society and Culture, 2023)
Abstract: Urbanization always give negative and positive influences to the development in any sectors. Impact that has been occurred from this process is not only be implicated to the aspect of spacing, but also to social, economy, and cultural aspect. The consequences of urbanization flow rapidly to urban area will cause the slum settlements spread widely, and the micro informal sectors are mushrooming. Informal sector is really developed rapidly and profitable, but it has a consequence to the increasing of poverty. This condition will disturb the urban structure because buffer area like "DAS" will be the target of settlement. The increasing of labor force which could not be involved in the industry are able to bring about internal conflict in the sector of manpower, like unemployment. Social and services facilities became increasingly as a reaction of user demand, however the benefit does not spread evenly because of high cost operating. The analysis of secondary data in this article/writing will try to show the urbanization condition in Indonesia and its developments.